Teachers’ intention to continue the use of online teaching tools post Covid-19 - Parul Bajaj; Adil Khan; Mosab I. Tabash; Suhaib Anagreh (Cogent Education, 2021)
Covid-19 has forced educators to switch to online teaching as the only viable option, whether through video lecturing or using other online teaching tools. Therefore, the study investigates university teachers’ perceptions towards their continuing intention of using the online platforms after Covid19 situations. To answer such questions, the present study conducted a survey of 242 faculties engaged in higher education teaching at assistant. We have conducted the present study using a sample of 242 faculties. Based on the framework of technology adoption model (TAM), this study investigates the research questions in the context of India. The study has adopted a mixed-method research design comprising both qualitative and quantitative techniques. The data were analyzed using partial least square structure equation modeling (PLS-SEM). The results of hypotheses testing indicate that all the hypotheses based on were accepted in the complete sample and for the men’s sample were accepted at p < 0.05 level. However, for the sample of women respondents, this was not the case. The study resulted that ease of use positively influences teachers’ attitude towards online teaching. This study provides theoretical contributions by applying the TAM to measure post-Covid-19 online teaching intention of teachers working at universities and college levels in India. It could help policyholders in the education sector to design appropriate strategies for online learning and teaching process. Though Covid-19 has adversely hit most of the industries, some industries might have benefited from this as well. Particularly, industries are thriving in the online market place.